Effective domestic remedies and the European Court of Human Rights : applications of the European Convention on Human Rights Article 13 - Reiertsen, Michael, 1976- (Cambridge, United Kingdom ; New York, NY : Cambridge University Press, 2022)
In Malone v. UK (Plenary 1984), the right to an effective domestic remedy in the European Convention on Human Rights Article 13 was famously described as one of the most obscure clauses in the Convention. Since then, the European Court of Human Rights has reinforced the scope and application of the right. Through an analysis of virtually all of the Court's judgments concerning Article 13, the book exhaustively accounts for the development and current scope and content of the right. The book also provides normative recommendations on how the Court could further develop the right, most notably how it could be a tool to regulate the relationship between domestic and international protection of human rights. In doing so, the book situates itself within larger debates on the enforcement of the entire Convention such as the principle of subsidiarity and the procedural turn in the Court's case law.
Setting the scene -- Analysis and selection of case law -- The requirement of effectiveness in abstract -- Historical and statistical overview -- Relationship with the rule on exhaustion of domestic remedies -- Scope of application -- The arguability test -- A relative standard -- General requirements and principles -- Access to justice -- Redress -- A normative and contextual reading -- Conclusions and recommendations.
Title from publisher's bibliographic system (viewed on 15 Aug 2022).
Keywords: European Court of Human Rights; Convention for the Protection of Human Rights and Fundamental Freedoms -- (1950 November 5); Human rights -- Europe; Remedies (Law) -- Europe; International and municipal law -- Europe